Continuous process field devices : using field communicators - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The CONTINUOUS PROCESS: Field Devices - Using Field Communicators training program, or unit, is designed to familiarize trainees with basic procedures for using field communicators to configure'smart' analog field devices. After completing this program, the trainees should be able to explain how to configure smart analog transmitters using a HART communicator, a Honeywell communicator, a Yokogawa communicator, and the Foxboro Local Display Module.
Keywords: Electronic analog computers -- Circuits; Electrical engineering; Engineering